Energy-resolved pulse profile changes in V 0332+53: Indications of wings in the cyclotron absorption line profile - D'Aì, Antonino; Maniadakis, Dimitrios K.; Ferrigno, Carlo; Ambrosi, Elena; Sokolova-Lapa, Ekaterina; Cusumano, Giancarlo; Becker, Peter A.; Burderi, Luciano; Del Santo, Melania; Di Salvo, Tiziana; Fürst, Felix; Iaria, Rosario; et al. (Astronomy & Astrophysics, 2025)
Aims. We aim to investigate the energy-resolved pulse profile changes of the accreting X-ray pulsar V 0332+53 focusing in the cyclotron line energy range, using the full set of available NuSTAR observations. Methods. We applied a tailored pipeline to study the energy dependence of the pulse profiles and to build the pulsed fraction spectra (PFS) for the different observations. We also studied the profile changes using cross-correlation and lag spectra. We re-analysed the energy spectra to search for links between the local features observed in the PFS and spectral emission components associated with the shape of the fundamental cyclotron line. Results. In the PFS data, with sufficiently high statistics, we observe a consistent behaviour around the cyclotron line energy. Specifically, two Gaussian-shaped features appear symmetrically on either side of the putative cyclotron line. These features exhibit minimal variation with source luminosity, and their peak positions consistently remain on the left and right of the cyclotron line energy. Associated with the cyclotron line-forming region, we interpret them as evidence for the resonant cyclotron absorption line wings, as predicted by theoretical models of how the cyclotron line profile should appear along the observer-s line of sight. A phase-resolved analysis of the pulse in the energy bands surrounding these features enables us to determine both the spectral shape and the intensity of the photons responsible for these peaks in the PFS. Assuming these features correspond to a spectral component, we used their shapes as priors for the corresponding emission components, finding a statistically satisfactory description of the spectra. To explain these results, we propose that our line of sight is close to the direction of the spin axis, while the magnetic axis is likely orthogonal to it.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Stars: magnetic field; Stars: neutron; X-rays: binaries; X-rays: individuals: V 0332+53